Prove that this is incorrect

  1. $g \circ f$ is surjective, but $g$ is not surjective.

  2. $f$ and $g$ are not injective, but $g \circ f$ is injective.

I know these both don't exist but, I don't really know how to formally prove them. Do I use proof by contradiction?

My attempt:

  1. We know $g \circ f$ is surjective and we want to show that $g$ is surjective. Let $y \in\mathbb R$. since $g \circ f$ is surjective, there exists an $b \in \mathbb R$ such that $g(f(b)) = y$. We set $c = f(b) \in\mathbb R,$ then $g(f(b))=g(c)=y$. So $g$ is surjective.

Is this how you're suppose to prove the question? I feel like I just proved that $g \circ f$ is surjective then $g$ is surjective but not the question above.

  1. I don't really know where to start with this one. Am I suppose to use proof by contradiction here?

For part 2, since $f$ is not injective, $\exists x,y \in \mathbb{R}$ with $x \neq y$ such that $f(x) = f(y)$. Then $(g \circ f)(x) = (g\circ f)(y)$.

Your proof of part 1 is correct. Since $g\circ f$ surjective $\implies$ $g$ surjective, there is no example of $g$, $f$ where $g \circ f$ is surjective, but $g$ is not.

Edit: Since $f(x)=f(y)$, we have $$(g\circ f)(x) = g(f(x)) = g(f(y)) = (g \circ f)(y).$$ Since $x \neq y$, it follows that $g \circ f$ is not injective.

  • $\begingroup$ Sorry, I don't get why "with 𝑥≠𝑦 such that 𝑓(𝑥)=𝑓(𝑦). Then (𝑔∘𝑓)(𝑥)=(𝑔∘𝑓)(𝑦)". Wouldn't it be (𝑔∘𝑓)(𝑥)≠(𝑔∘𝑓)(𝑦) if 𝑥≠𝑦? $\endgroup$ – bob Mar 20 at 2:04
  • $\begingroup$ @bob. If $f(x)$ and $f(y)$ are the same thing then $(g f)(x)=g (f(x))=g(f(y))=(g f)(y).$ $\endgroup$ – DanielWainfleet Mar 20 at 2:37

In general, it is simple to show "that such examples do not exist."

If someone asks you to show that:

examples of the set $A$ do not exist

then simply prove:

$A$ is the empty set.

Alternatively, suppose that that someone says,

Show that there are no examples of $x$ in $S$ such that $P(x)$, where $P(x)$ is some statement about $x$.

You are being asked to show:

not $[\exists x \in S$ such that $P(x)]$

That's very simple. Just prove:

$\forall x \in S$, not $P(x)$


If $gf$ is surjective then $$\Bbb R=\{(gf)(x):x\in \Bbb R\}=$$ $$=\{g(f(x)):x\in \Bbb R\}=$$ $$=\{g(y):y\in \{f(x):x\in \Bbb R\}\}\subset$$ $$\subset \{g(y):y\in \Bbb R\}\subset \Bbb R.$$ So $\Bbb R\subset \{g(y):y\in \Bbb R\}\subset \Bbb R.$

So $\{g(y):y\in \Bbb R\}=\Bbb R.$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.